A study to assess the knowledge and practice of women regarding dengue in rural area of Meerut, Uttar Pradesh, India - Kumar, Shishir; Shishir, Preeti; Lata, Kusum; Kudi, Surat Ram (International Journal Of Community Medicine And Public Health, 2024)
Background: Dengue affects 390 million people yearly. 70% global disease burden is from Asia. Every fourth person infected with dengue get sick and about one in 20 people infected with dengue develop severe dengue. Aim of this study was to assess the knowledge and practice of women regarding dengue in rural area of Meerut, U.P. Methods: A descriptive survey was done to conduct this study. Multistage random sampling was used to select study area and participants. Data has been collected from 50 participants. Self-developed knowledge questionnaire and checklist was prepared to measure knowledge and practices of people regarding knowledge and practices. Result: Most of the participants were between age group 18-23 years and were homemakers. All participants had previous knowledge about Dengue and source of information was TV/radio/newspaper for most of the participants. In this study 74% of participants has moderately adequate knowledge level, 16% had adequate and 10% had inadequate knowledge level. In regard to practices, 72% participant have satisfactorily practices, 20% had moderately satisfactorily practices and of 8 % participant non satisfactorily practices regarding prevention and management of dengue. Conclusion: Majority of participants had adequate knowledge and satisfactorily practices but still it is needed to organize awareness campaign to disseminate knowledge regarding dengue to community people of all age groups to improve their practices in this regard.